Assessment of Heavy Metals from Soil and Plants of Maiganaga Mining Site Gombe, Nigeria - Umar A.M,; Umar A.M,; Isiyaku A,; Bashir .M,; Sani M.B, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Environmental contaminants such as heavy metals released by activities related to mining deserves attention. The purpose of this study was to assess the level of heavy metal concentration in soil and plants of Maiganga coal mining site Gombe, Nigeria. Six leaves samples of Trees (Mangifera indica, Azadirachta indica, Eucalyptus globulus, Anacardium occidentale, Cassia javanica and Jatropha curcas) were collected at the reclaimed site and twelve soil samples were collected at both Mining and the Reclaimed sites at three different spots and at two different depths (15 & 30cm). Each soil and plant samples were dried, crushed and then sieved. Using aqua regia (hydrochloric acid by nitric acid, in a 3:1 volume ratio). Chromium (Cr), Cadmium (Cd), Arsenic (As), Iron (Fe), and Lead (Pb) concentrations were measured from the samples using Atomic Absorption Spectrometry. The results revealed that the concentrations of heavy metals (Cd, Cr, Fe, As, and Pb) in the soil from mining and reclaimed site are generally low and thus found to be within the World Health Organization (WHO) standard. At both 15 and 30cm iron (Fe) indicates high concentration in mining site than the reclaimed site. M. indica, E. globulus, J. curcas indicate high concentration of cadmium (Cd) and is higher than the WHO standard. The value obtained for cadmium (Cd) in A. indica is within the WHO maximum permissible limit. A. occidentale and C. javanica indicate low concentration of the heavy metals (Cd, Cr, Fe, As, and Pb). Arsenic (As) is the lowest concentrated heavy metal in both plant and soil samples. The low levels of As obtained in this study could be attributed to the less release of the heavy metals from the mining activity.